Fungsi Pesantren Dan Tuntutan Perubahan Sosial Pendidikan - Afga Sidiq Rifai (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: The development of education is no longer oriented cognitive intelligence alone, but already demanded how to prepare outputs ready to face real life the increasing number of unemployment in Indonesia is because our education has not provided supplies of life, so we need to follow the steps to improve existing social change. pesantren as an educational institution native Indonesia, as well as the oldest in the Indonesian education system could be a pioneer dorm life skills-based education History shows boarding a vital role in influencing this nation. Pesantren movement once the center of religious, educational, social, cultural, and political. Now this function ditutntut schools to be able to prepare graduates who are ready to plunge in the community, so pesantren must be entered on the functioning of the economy. Keywords: Schools, Economy, Social change, Education.